The Effect of Hegel's Philosophy of History on Goldziher's Method for Evaluating Hadiths - (:unkn) unknown (ILEM, 2021)
The West is known to have had interest in Islam since the 18th century through the transformative effect of the methods developed to examine religious sources within the framework of this interest in Islamic studies. Revealing the academic background and historical, ideological, psychological, religious, political and socio-cultural factors that have led orientalists working in the field of Islamic sciences is important for this field. This study will reveal in the context of Goldziher's method for evaluating hadiths how Orientalists had been influenced by the culture and civilization they emerged from and how these influences directed their studies on Islam. Studies that have drawn attention to how Goldziher adopted his method for evaluating hadiths and took inspiration from Hegel's philosophy of history prepared the intellectual background for the writing of this article. The study will first point out Goldziher's postition within the Orientalist tradition and then present his method for dating hadiths alongside his Muhammedanische Studien, which is considered the most important work upon which Goldhizer based his method. Hegel's philosophy of history will be explained in terms of the subject of the study, followed by a look into how Hegel's philosophy of history affected Goldziher's method for evaluating hadiths.
Keywords: Hegel; philosophy of history; Ignaz Goldziher; hadith dating; historical-critical method